2009
DOI: 10.1038/nature08488
|View full text |Cite
|
Sign up to set email alerts
|

Sleep deprivation impairs cAMP signalling in the hippocampus

Abstract: Millions of people regularly obtain insufficient sleep1. Given the impact of sleep deprivation on our lives, understanding the cellular and molecular pathways affected by sleep deprivation is clearly of social and clinical importance. One of the major effects of sleep deprivation on the brain is to produce memory deficits in learning paradigms that are dependent on the hippocampus2–5. In this study, we have identified a molecular mechanism by which brief sleep deprivation alters hippocampal function. Sleep dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

38
439
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 376 publications
(487 citation statements)
references
References 40 publications
38
439
1
Order By: Relevance
“…However, these differences in subunit ratios and mediated current after sleep deprivation have not been observed by other research groups. After 5 h of sleep deprivation by the gentle handling procedure (Ledoux et al 1996), no difference was observed in NMDA receptor-mediated current or in the NMDA/AMPA receptor ratio in CA1 (Vecsey et al 2009). These differences in NMDA receptor-mediated current could be attributed to sleep-deprivation techniques used in these two experimental designs.…”
Section: N-methyl-d-aspartate (Nmda) Receptor and A-amino-3-hydroxy-5mentioning
confidence: 92%
See 3 more Smart Citations
“…However, these differences in subunit ratios and mediated current after sleep deprivation have not been observed by other research groups. After 5 h of sleep deprivation by the gentle handling procedure (Ledoux et al 1996), no difference was observed in NMDA receptor-mediated current or in the NMDA/AMPA receptor ratio in CA1 (Vecsey et al 2009). These differences in NMDA receptor-mediated current could be attributed to sleep-deprivation techniques used in these two experimental designs.…”
Section: N-methyl-d-aspartate (Nmda) Receptor and A-amino-3-hydroxy-5mentioning
confidence: 92%
“…The NR2B subunit of the NMDA receptor has also been observed to decrease in the hippocampus as a result of REM sleep deprivation (Lopez et al 2008;Park et al 2012). Although both of these studies observed clear differences in trafficking and NMDA receptor-mediated current using extended periods of sleep deprivation, these findings conflict with findings from briefer periods of sleep deprivation (Vecsey et al 2009). Using electron microscopy, Kopp and colleagues found that 4 h of sleep deprivation by exposure to a novel environment and introduction to new nesting material increased the NR2A/NR2B NMDA-receptor subunit ratio as well as total NR2A subunits in the hippocampus (Kopp et al 2006;Longordo et al 2009).…”
Section: N-methyl-d-aspartate (Nmda) Receptor and A-amino-3-hydroxy-5mentioning
confidence: 97%
See 2 more Smart Citations
“…These findings close a causal loop that relates mnemonic gain to early-sleep neural synchronization. Animal studies have demonstrated that sleep triggers mnemonic reverberation at the level of action potentials 20 as well as calcium-dependent molecular events related to long-term memory storage 21,22 .…”
Section: R E V I E Wmentioning
confidence: 99%